2021
DOI: 10.5812/jhealthscope.116025
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Motorcycle Riding Behavior in Southeast of Iran

Abstract: Background: Motorcyclists are among the greatest vulnerable individuals of road accident victims. Their behavior has a significant correlation with increased injury and mortality rate. Determining the risky and unsafe behaviors of motorcycle drivers is necessary for preventing riders and other citizen from potential accident risks. Objectives: The aim of this study was to determine the risky driving behaviors of motorcyclists in Iran. Methods: A cross-sectional study was done in 2019 in Sistan and Baluchestan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Other studies [ 89 , 90 ] explored the effects of helmet laws related to any offsetting or improvement of the effects of motorcycle crashes [ 37 , 91 , 92 ]. Another study used a comprehensive crash database and analysis system via its Critical Accident Reporting Environment (CARE) [ 93 ]. The authors of [ 94 ] experimented with using a research database and provided high classification accuracy for detecting drivers’ emotions which result in smooth or aggressive driving.…”
Section: Taxonomymentioning
confidence: 99%
“…Other studies [ 89 , 90 ] explored the effects of helmet laws related to any offsetting or improvement of the effects of motorcycle crashes [ 37 , 91 , 92 ]. Another study used a comprehensive crash database and analysis system via its Critical Accident Reporting Environment (CARE) [ 93 ]. The authors of [ 94 ] experimented with using a research database and provided high classification accuracy for detecting drivers’ emotions which result in smooth or aggressive driving.…”
Section: Taxonomymentioning
confidence: 99%
“…MRBQ is a self-reported survey instrument that asks respondents to evaluate how often they take part in different behaviours with a Likert scale varying from 'never' to 'almost all the time', while riding the MTW (Sexton et al, 2004). Many researchers used different Likert scales in the MRBQ studies, such as 4-point scale (Putranto and Anjaya (2014); Sunday and Akintola (2010)), 5-point scale (Babajanpour et al, (2021);Setoodehzadeh et al, (2021)) and 6-point scale was widely adopted by Möller et al, (2020); Ospina-Mateus, Jiménez and López-Valdés (2021) and many others. The very first MRBQ is based on Manchester University's Driver Behaviour Questionnaire (DBQ) created by Reason et al (1990).…”
Section: Motorised Two-wheeler Rider Behaviour Questionnairementioning
confidence: 99%
“…Sexton et al, (2004); Elliott, Baughan and Sexton (2007); Özkan et al, (2012)), violation factors such as traffic violations, speed violations, and safety violations (e.g. Motevalian et al, (2011); Sumit et al, (2021); Setoodehzadeh et al, (2021)), stunt factor (e.g. Ospina-Mateus, Jiménez and López-Valdés (2021); Sunday and Akintola (2010)), safety equipment factor (e.g.…”
Section: Factors Influencing Mtw Rider Behaviourmentioning
confidence: 99%
“…The ndings of several studies have demonstrated the importance of different factors on the length of stay of burn injury patients. These factors include: demographics (age, sex), clinical data (admission time, burn size, etiology of burn, depth of burns and existence of inhalation injury), and biological parameters (serum electrolyte level changes), inhalational burns, among others (4)(5)(6)(7)(8). Burn injury has early and late outcomes, and Length of hospital stay (LOS) is one of the most important early outcomes.…”
Section: Introductionmentioning
confidence: 99%